GNI Corpus Version 1.0: Annotated Full-Text Corpus of to Support Biomedical Information Extraction - So-Yeon Oh; Ji-Hyeon Kim; Seo-Jin Kim; Hee-Jo Nam; Hyun-Seok Park (Genomics & Informatics)
Genomics & Informatics (NLM title abbreviation: Genomics Inform) is the official journal of the Korea Genome Organization. Text corpus for this journal annotated with various levels of linguistic information would be a valuable resource as the process of information extraction requires syntactic, semantic, and higher levels of natural language processing. In this study, we publish our new corpus called GNI Corpus version 1.0, extracted and annotated from full texts of Genomics & Informatics, with NLTK (Natural Language ToolKit)-based text mining script. The preliminary version of the corpus could be used as a training and testing set of a system that serves a variety of functions for future biomedical text mining.